Long-term nitrogen management strategies based on straw return improve soil carbon and nitrogen fractions and nitrogen use efficiency of maize in the Tumochuan Plain Irrigation District - Li, Wenbo; Qu, Jiawei; Gao, Julin; Yu, Xiaofang; Ma, Daling; Hu, Shuping; Borjigin, Qinggeer; Lu, Kexin (Frontiers in Plant Science, 2025)
IntroductionStraw return combined with rational nitrogen (N) fertilization plays a critical role in coordinating the transformation of soil organic carbon and nitrogen availability, thereby improving nitrogen use efficiency (NUE), crop yield, and soil fertility. However, the dynamics of soil carbon and nitrogen fractions under straw return with varying N inputs, and their specific contributions to NUE and yield, remain unclear.MethodsA three-year split-plot field experiment was conducted in the Tumochuan Plain Irrigation District. The main plots included deep plowing with straw return (DPR) and no straw return (RT), while subplots comprised four N application rates (0, 210, 255, and 300 kg ha-1). Soil carbon and nitrogen fractions, maize yield, NUE, and partial factor productivity of nitrogen (PFPN) were assessed.ResultsCompared to RT, DPR significantly improved soil nutrient levels and labile C and N fractions in the 0–40 cm soil layer. Maize yield, NUE, and PFPN increased by 17.28%, 18.24%, and 17.88%, respectively. Under DPR, a linear-plus-plateau model estimated the optimal N rate at 237.3 kg ha-1, reducing N input by 20.89% without compromising performance. Key contributors to NUE and PFPN included mineral nitrogen (MN), soil quality index (SQI), and dry matter accumulation (DMA), with relative contributions of 9.39%, 8.96%, and 8.49% to NUE, and 9.31%, 9.18%, and 8.99% to PFPN, respectively.DiscussionStraw return enhanced soil nitrogen availability and maize productivity by improving MN and SQI. Even with a 15–20% reduction in N application, DPR sustained high soil C and N fractions, yield, and NUE. These results offer practical guidance for optimizing N management under long-term straw return, with significant implications for sustainable maize production and soil fertility enhancement.